Traces of health—A landscape design task as a diagnostic aid for detecting mental burden? A qualitative focus group study - Niedermann, Christina; Anheyer, Dennis; Seeligmüller, Emily; Ostermann, Thomas (Frontiers in Psychology, 2023)
Background: Mental disorders are most common causes of illness worldwide. Studies on art and drawing tasks, such as the tree-drawing test have already proven their prognostic quality for the diagnosis of Alzheimer’s disease, depression or trauma. In the depiction of art in public space, gardens and landscapes are one of the oldest human forms of artistic expression. This study thus aims at exploring the impact of a landscape design task as a prognostic tool to detect mental burden. Material and Methods: 15 individuals (8 female) aged between 19 and 60 years completed the Brief Symptom Inventory BSI-18 and the State Trait Anxiety Inventory (STAI-S) before being asked to design a landscape in a 3x3m squared area. Material to be used included plants, flowers, branches and stones. The complete process of landscape design was videotaped and the tapes were analyzed in a two-step focus group analysis from a group of gardening trainees, psychology students and students of arts therapies. Results were condensed in a second step into major categories. Results: Scores of the BSI-18 showed a range of 2 to 21 points and STAI-S scores ranged between 29 and 54 points indicating a light to moderate mental burden. Focus group participants identified three mutually perpendicular major components associated with mental health: Movement and Activity”, “Material Selection & Design”, and “Connectedness to the task”. In a subsample of the three least and three most mentally stressed subjects (based on their GSI and STAI-S scorings), clear differences were found in body posture, action planning and the choice of material and aspects of design. Discussion: In addition to the well-known therapeutic potential of gardening, this study for the first time showed that gardening and landscape design contains diagnostic elements. Our preliminary findings are in coherence with similar research indicating a high association of movement and design patterns with mental burden. However, due to the pilot nature of the study, the results should be interpreted cautiously. Based on the findings further studies are currently planned.